2015
DOI: 10.1063/1.4917335
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent circuit effects on mode transitions in H2 inductively coupled plasmas

Abstract: It is well known experimentally that the circuit matching network plays an important role in the mode transition behavior of inductively coupled plasmas. To date, however, there have been no reports of numerical models being used to study the role of the matching circuit in the transition process. In this paper, a new two-dimensional self-consistent fluid model that couples the components of an equivalent circuit module is developed to investigate the effects of the equivalent circuit on the mode transition ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, it is difficult for the self-consistent multidimensional models to capture the discontinuity and hysteresis unless the external circuit module is taken into account. In this chapter, the conventional fluid model that describes the pure inductive mode is extended by including the capacitive mode and advanced by introducing an equivalent circuit module [26,27]. The diagram of equivalent circuit is illustrated in Figure 12.…”
Section: Discontinuous Mode Transition and Hysteresis Excited By Matcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult for the self-consistent multidimensional models to capture the discontinuity and hysteresis unless the external circuit module is taken into account. In this chapter, the conventional fluid model that describes the pure inductive mode is extended by including the capacitive mode and advanced by introducing an equivalent circuit module [26,27]. The diagram of equivalent circuit is illustrated in Figure 12.…”
Section: Discontinuous Mode Transition and Hysteresis Excited By Matcmentioning
confidence: 99%
“…Besides the above representative features, it still exhibits research values in the topics of reactive gas mixtures, such as O 2 [30], CF 4 /Ar [31], SO 2 [32], ammonia [33] and so on and double hysteresis loop [29], inverse hysteresis [34], spatial characteristics [35], optical emission [36], electrical diagnostics [37], instability of electronegative plasma source [38] and so on. To the author, the exploration of precursors that triggers hysteresis, for instance, metastables and multistep ionizations [13,21], electron energy distribution function [39], power coupling efficiency [40], sheath [24,41], external circuit [26,27] and nonlinear mechanisms [13] and so on, is the most attractive topic. The investigations greatly advance the improvements of analytical theory, numerical modeling, and experimental diagnostics of low-temperature plasma physics.…”
Section: Conclusion and Further Remarksmentioning
confidence: 99%
“…The model used in this paper consists of three parts, i.e., the electromagnetic module, equivalent circuit module, and fluid module. The model was elaborately described in our previous work [23] . Hence, in the present paper, only a brief introduction is given.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This is reasonable since in the real plasma sources it is already found that the variations in the azimuthal direction are indeed of minor importance and most of the present modelings in this type of reactor are conducted in radial and axial two-dimensional space. For more details related to this issue, reference [23] can be referred to.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation